The factors influencing participation in recycling program at Bandar Laguna Merbok / Nasrul Hazamir Muhd Nasir … [et al.] - Muhd Nasir, Nasrul Hazamir; Ibrahim, Muhammad Anas Syakirin (2017)
Recycling program in Malaysia had been launched by the government since year 1993 that involving 23 Local Authorities. Since the first program, the government had failed to achieve the objective of the recycling program for a several time. The failure of recycling program that launched by the government influenced by several factors. Currently, the government again introduce new recycling program in a different ways which is waste segregation that effective in September 2015. Thus, the study related to the recycling were chosen for this research study in order to know the factors influencing participation of Bandar Laguna Merbok’s residents in recycling program. The study will focus at Bandar Laguna Merbok and the respondent for this research is the residents of the residential area. The purpose of this study is to examine the relationship between recycling convenience, attitude towards recycling, knowledge on recycling, extrinsic and intrinsic motivations, and participation in recycling program. The study also will determine the most significant factor influencing participation of Bandar Laguna Merbok's residents in recycling program. A random sample of 351 respondents were selected to answer the questionnaires provided regarding to the recycling. Hopefully this research is able to identify the factor influencing participation of Bandar Laguna Merbok’s residents in recycling program that may be useful for municipal authority in Sungai Petani, Kedah.